Epigenetics of schizophrenia - Gebicke-Härter, Peter J. (Pharmacopsychiatry, 2012)
Investigations on gene variants as milestones in the development of schizophrenia have not fulfilled the enormous, initial expectations. Neither candidate gene approaches trying to associate single genes with the disorder, nor genome-wide association studies (GWAS), that have been welcomed more recently with great enthusiasm, could end the general disappointment associated with these strategies. Owing to very large numbers of samples and most advanced sequencing technologies, some variants have been found but their effects, even in combination are very small. In summary, most of the tentative heritability of schizophrenia remains unexplained. More hope to find mechanisms connecting genes with the disorder lies in analyses of the epigenome with technologies developed during the last 10 or 15 years and undergoing more and more refinement recently. Although investigations on interactions between DNA methylation patterns and histone modifications will probably be the greatest challenge in molecular genetics for the next decades, they appear to be the most promising approaches on complex brain disorders that typically show a high dependence on environmental factors.